2014
DOI: 10.1089/jmf.2013.0065
|View full text |Cite
|
Sign up to set email alerts
|

Citric Acid Effects on Brain and Liver Oxidative Stress in Lipopolysaccharide-Treated Mice

Abstract: Citric acid is a weak organic acid found in the greatest amounts in citrus fruits. This study examined the effect of citric acid on endotoxin-induced oxidative stress of the brain and liver. Mice were challenged with a single intraperitoneal dose of lipopolysaccharide (LPS; 200 lg/kg). Citric acid was given orally at 1, 2, or 4 g/kg at time of endotoxin injection and mice were euthanized 4 h later. LPS induced oxidative stress in the brain and liver tissue, resulting in marked increase in lipid peroxidation (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
82
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(89 citation statements)
references
References 47 publications
(43 reference statements)
7
82
0
Order By: Relevance
“…Citric acid can attenuate lipopolysaccharide (LPS) induced liver injury including DNA fragmentation with a decrease of caspase-3 and serum transaminase elevations (Abdel-Salam et al, 2014). Our results have shown that citric acid has an LC50 of 1.58 ± 0.08 mg, which is not as toxic as the other components tested.…”
Section: Discussionmentioning
confidence: 66%
“…Citric acid can attenuate lipopolysaccharide (LPS) induced liver injury including DNA fragmentation with a decrease of caspase-3 and serum transaminase elevations (Abdel-Salam et al, 2014). Our results have shown that citric acid has an LC50 of 1.58 ± 0.08 mg, which is not as toxic as the other components tested.…”
Section: Discussionmentioning
confidence: 66%
“…The present results were in accordance with previous studies on hypoxia/reoxygenation‐induced cardiomyocytes, which showed that citric acid significantly down‐regulated the gene expression of cleaved Caspase‐3 and decreased cell apoptotic rate (Tang et al, ). Abdel‐Salam et al () also provided evidence that citric acid significantly decreased the hepatic Caspase‐3 immunoreactivity in lipopolysaccharide‐treated mice. Involved in removal of intracellular ROS and repair of oxidative damage, p53 was reported to inhibit the cell proliferation and drive a temporary cell cycle arrest (Bensaad et al, ; Budanov, Sablina, Feinstein, Koonin, & Chumakov, ; Gatz & Wiesmüller, ; Sablina et al, ; Yoon, Nakamura, & Arakawa, ).…”
Section: Discussionmentioning
confidence: 95%
“…Similar results were observed in the study on large yellow croaker‐( Larimichthys crocea ) fed high doses of dietary plant protein, which showed that dietary citric acid alleviated intestinal oxidative damage (lipid peroxidation and oxidative carbonyl protein) through increasing intestinal T‐AOC and activities of SOD and Cu‐Zn SOD (Zhang et al, ). Another study on mice showed that ingestion of citric acid significantly attenuated LPS‐induced lipid peroxidation (in terms of MDA) in the brain tissue through increasing glutathione peroxidase (GPx) and paraoxonase 1 (PON1) activities (Abdel‐Salam et al, ). The increasing intestinal oxidative stress could cause the peroxidation of key biomolecules involved in various pathological processes including intestinal mucosal injury and digestive malfunctions (Ames, ; Halliwell, ; Jiang et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As one of the most important organic acids, citric acid (CA) is primary found in citrus fruits, such as lemon, grapefruit and orange (Abdel-Salam et al, 2014). CA is a type of a-hydroxy acid which has been widely used in food, beverage, chemical industries for many years (Xu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%